Conceptos, aportes y teorías: ¿Cómo diseñar una ciudad ideal? (2021)
In the article we propose the different perspectives that are given by scientists, urban planners, architects and writers regarding how they shape an ideal city; Each one Emphasizes how the design of this should be, thanks to their contributions we can identify the characteristics and on which the ideal city is based.